METODE PEMILIHAN FACADE KACA SINGLE GLAZED PADA BANGUNAN - Fuk Jin Oei; Sudarno P Tampubolon; Daniel (UKI Press, 2025)
The building façade must be carefully designed from the early planning stage. Given the wide variety of single-glazed glass types, selecting an appropriate glass façade is not a simple task. In practice, glass selection is generally based solely on cost considerations. This study proposes a glass façade selection method that incorporates comfort performance as a primary criterion. In addition to comfort, physical properties and cost factors are also considered. The comfort parameters evaluated in this study include thermal comfort and visual comfort derived from the glass properties. A total of fifty-five (55) single-glazed glass samples, consisting of float glass, tinted glass, and reflective glass, were analyzed. The results indicate that the proposed method can effectively support glass façade selection. For float glass, increasing glass thickness leads to improved comfort performance. For tinted glass, green-colored glass with a thickness of 6 mm exhibits the best comfort performance with a value of 6.6. Meanwhile, for reflective glass, classic green reflective glass achieves the highest comfort performance value of 7.0 at a thickness of 6 mm. Among all single-glazed glasses (tinted and reflective) with a thickness of 6 mm, classic green reflective glass demonstrates the best overall comfort performance.